2017
DOI: 10.3389/fnins.2017.00326
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticographic Temporal Alteration Mapping: A Clinical Technique for Mapping the Motor Cortex with Movement-Related Cortical Potentials

Abstract: We propose electrocorticographic temporal alteration mapping (ETAM) for motor cortex mapping by utilizing movement-related cortical potentials (MRCPs) within the low-frequency band [0.05-3] Hz. This MRCP waveform-based temporal domain approach was compared with the state-of-the-art electrocorticographic frequency alteration mapping (EFAM), which is based on frequency spectrum dynamics. Five patients (two epilepsy cases and three tumor cases) were enrolled in the study. Each patient underwent intraoperative dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…11,13,[32][33][34] Given these landmarks, in clinical practice, performing ECoG mapping prior to ECS is reasonable and can serve to reduce the number of electrodes for ECS reconfirmation. Two aspects of our study are particularly new and noteworthy: (1) a very wide spectrum of intrinsic activities, including both very slow cortical components (MRCPs) recorded using a long time constant (10 seconds) and fast activities of ERS/ERD, were employed across the primary motor cortices; and (2) the M1 mapping using MRCP/ERS/ERD was directly compared with ECS, and a clear clinical application was specified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,[32][33][34] Given these landmarks, in clinical practice, performing ECoG mapping prior to ECS is reasonable and can serve to reduce the number of electrodes for ECS reconfirmation. Two aspects of our study are particularly new and noteworthy: (1) a very wide spectrum of intrinsic activities, including both very slow cortical components (MRCPs) recorded using a long time constant (10 seconds) and fast activities of ERS/ERD, were employed across the primary motor cortices; and (2) the M1 mapping using MRCP/ERS/ERD was directly compared with ECS, and a clear clinical application was specified.…”
Section: Discussionmentioning
confidence: 99%
“…The score accuracy of spatial concordance with ECS was as good as or better than those in previous studies. 11,13,[32][33][34] Given these landmarks, in clinical practice, performing ECoG mapping prior to ECS is reasonable and can serve to reduce the number of electrodes for ECS reconfirmation. This strategy is especially true for upper limb mapping rather than face mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, many studies have identified and confirmed HGA as a robust neural correlate of cognition and behavior. These studies encompass motor (Crone et al, 1998 ; Leuthardt et al, 2004 ; Canolty et al, 2006 ; Miller et al, 2007 , 2010 ; Li et al, 2017 ; Wu et al, 2017 ; Pan et al, 2018 ; Gruenwald et al, 2019 ; Thomas et al, 2019 ), somatosensory (Menon et al, 1996 ; Canolty et al, 2006 ; Genetti et al, 2015 ; Prueckl et al, 2015 ; Wahnoun et al, 2015 ), auditory (Crone et al, 2001 ; Ray et al, 2003 ; Towle et al, 2008 ; Gaona et al, 2011 ; Potes et al, 2012 ; Sturm et al, 2014 ; Tamura et al, 2016 ), language (Leuthardt et al, 2004 ; Sinai et al, 2005 ; Towle et al, 2008 ; Pei et al, 2011a , b ; Arya et al, 2017 , 2018 , 2019 ; Kambara et al, 2018 ; Williams Roberson et al, 2020 ), and visual (Ramot et al, 2012 ; Matsuzaki et al, 2013 ; Boucher et al, 2015 ; Miller et al, 2016 ; Rupp et al, 2017 ; Schalk et al, 2017 ; Kapeller et al, 2018a , b ; Nakai et al, 2018 ; Wittevrongel et al, 2020 ) functions, as well as various types of cognitive (e.g., memory) tasks (Sederberg et al, 2003 ; Canolty et al, 2006 ; Axmacher et al, 2007 ; Lachaux et al, 2007 ; Ray et al, 2008 ; Burke et al, 2014 ; Kunii et al, 2014 ; Serruya et al, 2014 ; Noy et al, 2015 ; Ueda et al, 2015 ). Further studies demonstrated the role of HGA during resting state and sleep (Hirai et al, 1999 ; Freeman et al, 2000 ; He et al, 2008 ; Geller et al, ...…”
Section: Introductionmentioning
confidence: 99%
“…The ability to precisely and robustly locate the cortical areas involved in cognitive and behavioral tasks from HGA has given rise to functional mapping applications that are now widely used in the presurgical evaluation of epilepsy and tumor patients. In these functional mapping applications, HGA identifies sensorimotor regions (Crone et al, 1998 ; Sinai et al, 2005 ; Leuthardt et al, 2007 ; Brunner et al, 2009 ; Hermes et al, 2010 ; Ruescher et al, 2013 ; Genetti et al, 2015 ; Prueckl et al, 2015 ; Wahnoun et al, 2015 ; Wu et al, 2017 ), expressive language regions and the auditory cortex (Sinai et al, 2005 ; Towle et al, 2008 ; Edwards et al, 2010 ; Roland et al, 2010 ; Pei et al, 2011b ; Babajani-Feremi et al, 2016 ; Arya et al, 2017 , 2018 , 2019 ; Kambara et al, 2018 ), visual regions (Matsuzaki et al, 2013 ; Kapeller et al, 2018b ; Nakai et al, 2018 ; Wittevrongel et al, 2020 ), and memory regions (Axmacher et al, 2007 ; Burke et al, 2014 ; Kunii et al, 2014 ). This identification of cortical regions is commonly realized by a statistical test that compares task-related changes in HGA to a resting-state condition.…”
Section: Introductionmentioning
confidence: 99%